KESEHATAN JIWA PEGAWAI POLKESYO DIMASA PANDEMI COVID-19 MENTAL HEALTH OF POLKESYO EMPLOYEES DURING THE COVID-19 PANDEMIC - Sarka Ade Susana; Nunuk Sri Purwanti; Rosa Delima Ekwantini; Sapta Rahayu Noamperani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Health is not only about physical condition but also mental condition. Mental health is an integral part of every individual. A healthy soul is described as free from complaints and in a peaceful and calm state. The disease outbreak called Coronavirus Disease 2019 (COVID-19) does not only attack physical health, but also has an impact on mental health. Those who work especially in an institution will affect its performance. Polkesyo as an educational institution as well as a Public Service Agency (BLU) requires employee mental health data as a basis for formulating appropriate policies so that they can anticipate future mental health problems. The aim of the study was to get an overview of the mental health of the employees of the Yogyakarta Ministry of Health Poltekkes. The research design is descriptive. Obtained 112 samples from 374 populations with a combination of snowball technique and saturated sampling using the Self Reporting Questionary (SRQ) instrument with google form. Data analysis technique uses frequency distribution. The results of the study were that most of the respondents were mentally healthy (58%). A small portion with mental emotional disorders is quite healthy, there are 33.9% and 8.1% are unhealthy. Emotional mental disorders are most often reflected in the form of feelings of insecurity and discomfort manifested by avoidance of certain people, places and activities (17.9%), feelings of anxiety, tension and worry (17%), and there are 1.8% even though they are small but very dangerous, namely thoughts of wanting to end one's life (suicide). The conclusion is that the mental health of most of the respondents is mentally healthy, a small portion is quite healthy and less healthy.